Thai information and communication technology student teacher complex problem-solving skills - Natchanun Sermsri; Aukkapong Sukkamart; Thiyaporn Kantathanawat (My University, 2021)
From the study’s qualitative analysis, 5 latent variables and 21 observed variables concerning complex problem-solving (CPS) skills were identified and subsequently used in a questionnaire on a sample of 214 Thai education professionals teaching information and communication technology (ICT)-related student teachers in one of 31 Thai Rajabhat (teaching) Universities. Goodness-of-fit and descriptive statistical analysis (mean and standard deviation) were analysed by using IBM® Statistical Package for the Social Sciences® for Windows version 21, while the second-order confirmatory factor analysis used LISREL 9.10. The results revealed that the educators perceived information literacy (1.00), analytical thinking (0.96), self-control (0.93), knowledge application (0.90) and planning ability (0.85) as the most important for the student teachers’ CPS skills. Moreover, the results revealed that each teacher’s opinion on CPS skill indicators was at a ‘high agreement’ level. Therefore, it suggested that the results can be used by Thailand’s Ministry of Education and other ICT-related education agencies in developing CPS skill programmes for Thai student teachers.


Keywords: CPS, ICT, Information literacy, preservice teachers, Thailand
Keywords: LISREL; IBM; Christian ministry; Sample (material); Technology-Enhanced Education Studies